Development of ZnFeCe Layered Double Hydroxide Incorporated Thin Film Nanocomposite Membrane with Enhanced Separation Performance and Antibacterial Properties - Balçık, Çiğdem; Ozbey-Unal, Bahar; Sahin, Busra; Buse Aydin, Ecem; Cifcioglu-Gozuacik, Bengisu; Keyikoglu, Ramazan; Khataee, Alireza (Mdpi, 2023)
Developing thin-film nanocomposite (TFN) membranes by incorporating nanomaterials into the selective polyamide (PA) layer is an effective strategy to improve separation and antibacterial properties. In this study, TFN nanofiltration (NF) membranes were fabricated by interfacial polymerization of piperazine (PIP) and trimesoyl chloride (TMC) with the addition of Zinc-Iron-Cerium (ZnFeCe) layered double hydroxide (LDH). The improved surface hydrophilicity of TFN membranes was investigated by water contact angle analyses and pure water flux measurements. Successful production of the PA layer on the membrane surface was determined by Fourier-transform infrared (FTIR) analysis. Atomic Force Microscope (AFM) images showed that the addition of LDH into the membrane resulted in a smoother surface. The scanning electron microscope and energy-dispersive X-ray spectroscopy (SEM/EDS) mapping of TFN membrane proved the presence of Ce, Fe, and Zn elements, indicating the successful addition of LDH nanoparticles on the membrane surface. TFN 3 membrane was characterized with the highest flux resulting in 161% flux enhancement compared to the pristine thin film composite (TFC) membrane. All membranes showed great rejection performances (with a rejection higher than 95% and 88% for Na2SO4 and MgSO4, respectively) for divalent ions. Additionally, TFN membranes exhibited excellent antibacterial and self-cleaning properties compared to the pristine TFC membrane.
Keywords: thin film membrane; layered double hydroxide; nanofiltration; salt removal